2015
DOI: 10.1007/7651_2015_305
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Derivation of Melanocytes from Embryonic Neural Crest Stem Cells

Abstract: During development, melanocyte progenitors originate from the neural crest, a transient embryonic structure in vertebrates that gives rise to a variety of cell types including neurons and glia of the peripheral nervous system, smooth muscle cells of the cardiovascular system, chondrocytes and osteoblasts of the craniofacial elements, and pigment cells in the skin. In this chapter, we describe a method for the differentiation of multipotent embryonic neural crest stem cells into differentiated pigmented melanoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Several studies have been performed in vivo to address the developmental potential of individual NC cells by retrovirus-mediated gene transfer or dye injection to label cell lineages [196,197,198]. These studies showed that at least some NC cells generate different cell types in vivo, including smooth muscle cells, neurons, glia, and melanocytes [198,199]. Cultured NC cells from mouse neural tube explants derived prior to NC cell migration demonstrated their multipotency in vitro [200].…”
Section: Wnt In Nc Multipotency and Fate Determinationmentioning
confidence: 99%
“…Several studies have been performed in vivo to address the developmental potential of individual NC cells by retrovirus-mediated gene transfer or dye injection to label cell lineages [196,197,198]. These studies showed that at least some NC cells generate different cell types in vivo, including smooth muscle cells, neurons, glia, and melanocytes [198,199]. Cultured NC cells from mouse neural tube explants derived prior to NC cell migration demonstrated their multipotency in vitro [200].…”
Section: Wnt In Nc Multipotency and Fate Determinationmentioning
confidence: 99%
“…In the mouse system, melanocyte generation from embryonic NCSC has been performed by addition of SCF and END3 in the culture medium (Shakhova and Sommer, 2015). In the human system, protocols of melanocyte differentiation from PSCs through a NC stage have also been described.…”
Section: Stem Cell-based Models Of Human Neural Crestsmentioning
confidence: 99%
“…Shakhova and Sommer [84] have established a differentiation approach to generate melanocytes from embryonic NCSCs in 10 days by the addition of a cocktail of specific growth factors such as ET-3 and mouse SCF. Their study showed that after 10-day differentiation, the majority of NCSCs presented a melanocytic phenotype indicating the in vitro differentiation ability of NCSCs into melanocytes.…”
Section: Clinical Applications Of Ncscsmentioning
confidence: 99%